Natural resource exports, foreign aid and terrorism - Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
Linkages between foreign aid, terrorism and natural resource (fuel and iron ore) exports are investigated in this study. The focus is on 78 developing countries with data for the period 1984 to 2008. The generalised method of moment is employed as empirical strategy. Three main foreign aid variables are used for the analysis, namely: bilateral aid, multilateral aid and total aid. The corresponding terrorism variables employed are: domestic terrorism, transnational terrorism, unclear terrorism and total terrorism. The following findings are established. First, the criteria informing the validity of specifications corresponding to iron ore exports do not hold. Second, there is evidence of convergence in fuel exports. Third, whereas the unconditional impacts of aid dynamics are not significant, the unconditional impacts of terrorism dynamics are consistently positive on fuel exports. Fourth, the interaction between terrorism and aid dynamics consistently display negative signs, with corresponding modifying aid thresholds within respective ranges. Unexpected signs are elicited and policy implications discussed. Given the unexpected results, an extended analysis is performed in which net effects are computed. These net effects are constitutive of the unconditional effect from terrorism and the conditional impacts from the interaction between foreign aid and terrorism dynamics. Based on the extended analysis, bilateral aid and total aid modulate terrorism dynamics to induce net positive effects on fuel exports while multilateral aid moderates terrorism dynamics to engender negative net effects on fuel exports. The research improves extant knowledge on nexuses between resources, terrorism and foreign aid.
Keywords: F40; F23; F35; Q34; O40; 330; Foreign Aid; Exports; Natural Resources; Terrorism; Economic Development